The effect of children on earnings inequality among men - Astrid Kunze (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study investigates empirically whether fatherhood has a causal effect on earnings inequality among men. Rich register data on life cycle employment and earnings, and fertility histories on brother couples are used to estimate flexible earnings regressions with fixed factors. The main result is that higher earners are more likely to become a father, and not that children make fathers earn higher incomes. Furthermore, men who remain childless and/or unmarried, are on relatively low earnings profiles and contribute therefore significantly to the earnings inequality among men. Finally, most of the earnings variation comes from first childbirth, not from further children or from marriage.
Keywords: J16; J24; J31; 330